 Kathy Williams

2021-12-31

Solve the following equation algebraically. Explain your process.
$0=18{x}^{4}+87{x}^{3}+3{x}^{2}-108x$ Hattie Schaeffer

Step 1
Given equation is:
$18{x}^{4}+87{x}^{3}+3{x}^{2}-108x=0$
Taking 3x as common term we get,
$3x\left(6{x}^{3}+29{x}^{2}+x-36\right)=0$
So either,
$3x=0$
$x=0$
Or $6{x}^{3}+29{x}^{2}+x-36=0$
Step 2
Splitting up the second and third terms we get,
$6{x}^{3}-6{x}^{2}+35{x}^{2}-35x+36x-36=0$
$6{x}^{2}\left(x-1\right)+35x\left(x-1\right)+36\left(x-1\right)=0$
Taking $\left(x-1\right)$ as common term we get,
$\left(x-1\right)\left(6{x}^{2}+35x+36\right)=0$
Using middle term factorization we get,
$\left(x-1\right)\left(6{x}^{2}+8x+27x+36\right)=0$
$\left(x-1\right)\left[2x\left(3x+4\right)+9\left(3x+4\right)\right]=0$
$\left(x-1\right)\left(3x+4\right)\left(2x+9\right)=0$
$\left(x-1\right)=0;\left(3x+4\right)=0;\left(2x+9\right)=0$
$x=1;x=-\frac{4}{3};x=-\frac{9}{2}$
Hence the roots of the given equation is:
$x=0;x=1;x=-\frac{4}{3};x=-\frac{9}{2}$. eskalopit

$18{x}^{4}+87{x}^{3}+3{x}^{2}-108x$
Factor out common term 3x: $3x\left(6{x}^{3}+29{x}^{2}+x-36\right)$
$=3x\left(6{x}^{3}+29{x}^{2}+x-36\right)$
Factor $6{x}^{3}+29{x}^{2}+x-36:\left(x-1\right)\left(3x+4\right)\left(2x+9\right)$
$=3x\left(x-1\right)\left(3x+4\right)\left(2x+9\right)$ karton

We move all terms to the left:
$0-\left(18x+87x+3{x}^{2}-108x\right)=0$
We add all the numbers together, and all the variables
$-\left(18x+87x+3{x}^{2}-108x\right)=0$
We get rid of parentheses
$-3{x}^{2}-18x-87x+108x=0$
We add all the numbers together, and all the variables
$-3{x}^{2}+3x=0$
a=-3; b=3; c=0;
$\mathrm{△}={b}^{2}-4ac$
$\mathrm{△}={3}^{2}-4\cdot \left(-3\right)\cdot 0$
$\mathrm{△}=9$
The delta value is higher than zero, so the equation has two solutions.
NSK
We use following formulas to calculate our solutions:
$\sqrt{\mathrm{△}}=\sqrt{9}=3$
${x}_{1}=\frac{-b-\sqrt{\mathrm{△}}}{2a}=\frac{-\left(3\right)-3}{2\cdot -3}=\frac{-6}{-6}=1$
${x}_{2}=\frac{-b+\sqrt{\mathrm{△}}}{2a}=\frac{-\left(3\right)+3}{2\cdot -3}=\frac{0}{-6}=0$ alenahelenash

Step 1: Factor out the common factor of $x$ from each term:
$0=x\left(18{x}^{3}+87{x}^{2}+3x-108\right)$
Step 2: Now, we can focus on solving the equation $18{x}^{3}+87{x}^{2}+3x-108=0$. To find the solutions, we can use various methods such as factoring, the rational root theorem, or numerical methods. In this case, we will use factoring by grouping.
Step 3: Group the terms in pairs:
$18{x}^{3}+87{x}^{2}+3x-108=\left(18{x}^{3}+3x\right)+\left(87{x}^{2}-108\right)$
Step 4: Factor out the greatest common factor from each pair:
$18{x}^{3}+3x+87{x}^{2}-108=3x\left(6{x}^{2}+1\right)+3\left(29{x}^{2}-36\right)$
Step 5: Simplify each pair:
$3x\left(6{x}^{2}+1\right)+3\left(29{x}^{2}-36\right)=3x\left(6{x}^{2}+1\right)+3\left(29{x}^{2}-36\right)$
Step 6: Notice that we have a common binomial factor of $\left(6{x}^{2}+1\right)$:
$3x\left(6{x}^{2}+1\right)+3\left(29{x}^{2}-36\right)=3x\left(6{x}^{2}+1\right)+3\left(29{x}^{2}-36\right)$
Step 7: Factor out the common factor of $\left(6{x}^{2}+1\right)$:
$3x\left(6{x}^{2}+1\right)+3\left(29{x}^{2}-36\right)=3x\left(6{x}^{2}+1\right)+3\left(29{x}^{2}-36\right)$
Step 8: Now, we have factored the equation as follows:
$0=x\left(6{x}^{2}+1\right)+3\left(29{x}^{2}-36\right)$
Step 9: Set each factor equal to zero and solve for $x$:
$x=0$ or $6{x}^{2}+1=0$ or $29{x}^{2}-36=0$
Step 10: Solving the quadratic equation $6{x}^{2}+1=0$ gives us:
$6{x}^{2}+1=0⟹{x}^{2}=-\frac{1}{6}⟹x=±\sqrt{-\frac{1}{6}}$
Step 11: Solving the quadratic equation $29{x}^{2}-36=0$ gives us:
$29{x}^{2}-36=0⟹{x}^{2}=\frac{36}{29}⟹x=±\sqrt{\frac{36}{29}}$
Step 12: Simplifying the square roots gives us the final solutions:
$x=0$, $x=±\sqrt{-\frac{1}{6}}$, $x=±\sqrt{\frac{36}{29}}$
Therefore, the solutions to the equation $0=18{x}^{4}+87{x}^{3}+3{x}^{2}-108x$ are $x=0$, $
x=±\sqrt{-\frac{1}{6}}$
, and $x=±\sqrt{\frac{36}{29}}$. star233

To solve the equation algebraically, we need to find the values of x that satisfy the equation. We can start by factoring out the common factor of x:
$0=x\left(18{x}^{3}+87{x}^{2}+3x-108\right)$
Now, we have two cases to consider:
1. $x=0$
When x equals 0, the equation becomes:
$0=0$
This is always true, so x = 0 is a solution.
2. $18{x}^{3}+87{x}^{2}+3x-108=0$
To solve this cubic equation, we can use various methods such as factoring, synthetic division, or the rational root theorem. However, in this case, it is not easy to find rational roots. Therefore, we can use numerical methods or calculators to approximate the roots.
Let's use a numerical method to find an approximate solution. By substituting some values for x, we can observe the behavior of the expression and estimate the roots.
Substituting x = -2, we get:
$18\left(-2{\right)}^{3}+87\left(-2{\right)}^{2}+3\left(-2\right)-108=-216+348-6-108=18$
Since the expression evaluates to a positive value, we can conclude that there is a root between x = 0 and x = -2.
Similarly, substituting x = 1, we get:
$18\left(1{\right)}^{3}+87\left(1{\right)}^{2}+3\left(1\right)-108=18+87+3-108=0$
The expression evaluates to 0, indicating that x = 1 is a root.
Now we have found two roots: x = 0 and x = 1. To find the remaining roots, we can perform polynomial long division or synthetic division to obtain a quadratic equation. However, since the original equation is quite lengthy, performing these operations in this short form would be cumbersome.
Therefore, to summarize:
The solutions to the equation $0=18{x}^{4}+87{x}^{3}+3{x}^{2}-108x$ are:
$x=0$ (found by factoring out x)
$x=1$ (approximated using numerical methods)
To find the remaining solutions, further algebraic manipulations are required.

Do you have a similar question?